Pengaruh Kualitas Layanan Terhadap Loyalitas Nasabah Dalam Perbankan Syariah Di Provinsi Lampung Pada Tahun 2023 - Suwardi, Gio Pilanditha; Haryadi, Anton; Wimbawani, Wiwik (Jurnal Ekonomi Syariah dan Pariwisata Halal, 2023)
This research was carried out in order to understand the impact of service quality on Sharia Banking customer loyalty in Lampung Province in 2023. This research is classified as quantitative research with an emphasis on calculation results. The results of the reliability testing carried out obtained results with a service quality variable with an Alpha Coefficient of 0.949 and a customer loyalty variable with an Alpha Coefficient of 0.842. The questionnaire was distributed to a total of 100 research subjects. The calculated t value of the service quality variable is 1,247. This explains that the calculated t is greater than the specified t table value (4.153 > 1.989), meaning the result is a positive significance level of 0.000 which is smaller than 0.05. So the alternative hypothesis (Ha) can be accepted, while the null hypothesis (Ho) can be rejected. So it can be concluded that there is a positive impact between service quality and Sharia Banking customer loyalty in Lampung Province in 2023.